Neurotoxicity of the pesticide rotenone on neuronal polarization: A mechanistic approach - Bisbal, Mariano (2019)
Neurons are the most extensive and polarized cells that display a unique single long axon and multiple dendrites, which are compartments exhibiting structural and functional differences. Polarity occurs early in neuronal development and it is maintained by complex subcellular mechanisms throughout cell life. A well-defined and controlled spatio-temporal program of cellular and molecular events strictly regulates the formation of the axon and dendrites from a non-polarized cell. This event is critical for an adequate neuronal wiring and therefore for the normal functioning of the nervous system. Neuronal polarity is very sensitive to the harmful effects of different factors present in the environment. In this regard, rotenone is a crystalline, colorless and odorless isoflavone used as insecticide, piscicide and broad spectrum pesticide commonly used earlier in agriculture. In the present review we will summarize the toxicity mechanism caused by this pesticide in different neuronal cell types, focusing on a particular biological mechanism whereby rotenone could impair neuronal polarization in cultured hippocampal neurons. Recent advances suggest that the inhibition of axonogenesis produced by rotenone could be related with its effect on microtubule dynamics, the actin cytoskeleton and their regulatory pathways, particularly affecting the small RhoGTPase RhoA. Unveiling the mechanism by which rotenone produces neurotoxicity will be instrumental to understand the cellular mechanisms involved in neurodegenerative diseases influenced by this environmental pollutant, which may lead to research focused on the design of new therapeutic strategies.